Rancang Bangun Alat Parut Kelapa Otomatis Berbasis Atmega 8535 - Osra Wiro Musli; Aslimeri Asimeri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
Nowday, the development of technology is growing rapidly, this has an impact on practical life. One of them is coconut grating. in grating coconut people usually used coconut grating. but still rely on human power in grated procces. People use grated coconut from coconut plants. The result of grated coconut that can be used as an ingredient in food making, in order to get grated coconut, commonly people still used traditional way to take it.to overcome the situation, this thesis is designed to make it easier without washing energy and save time. by using sensor tcs3200 to detect color and hcsr 04 to respond distance. beside this project there I a buzzer makes sound when the coconut is finished being grated. the design of this project uses experimental method that consist of hardware and software design. this tool uses microcontroller atmega8535 as control centre of the tool . Dc motor permanent megnet as arm drive motor induction for main grater